2023
DOI: 10.1159/000529475
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Efficacy of Hepatic Artery Infusion Chemotherapy with or without Lenvatinib for Unresectable Hepatocellular Carcinoma

Abstract: Background: For patients with advanced hepatocellular carcinoma (HCC), hepatic artery infusion chemotherapy (HAIC) is a common and mature treatment, but the safety and efficacy of HAIC combined with lenvatinib for advanced HCC patient treatment remains unclear. Therefore, this study compared the safety and efficacy of HAIC with or without lenvatinib in unresectable HCC patients. Methods: We retrospectively analyzed 13 unresectable advanced HCC patients who received HAIC monotherapy or combination therapy of HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Moreover, several observational studies have reported that sequential therapy with LEN and TACE provides a survival benefit following the progression of u-HCC [ 10 , 11 ]. Fang et al reported improved survival outcomes in patients with HCC treated with LEN combined with HAIC [ 12 ]. While the efficacy of LEN combined with TIT, targeting intrahepatic tumors, has been demonstrated in intermediate-stage HCC, a recent clinical trial has shown its effectiveness even in advanced-stage HCC [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several observational studies have reported that sequential therapy with LEN and TACE provides a survival benefit following the progression of u-HCC [ 10 , 11 ]. Fang et al reported improved survival outcomes in patients with HCC treated with LEN combined with HAIC [ 12 ]. While the efficacy of LEN combined with TIT, targeting intrahepatic tumors, has been demonstrated in intermediate-stage HCC, a recent clinical trial has shown its effectiveness even in advanced-stage HCC [ 13 ].…”
Section: Introductionmentioning
confidence: 99%